Association of Epstein-Barr virus (EBV) with lung cancer: meta-analysis - Chen, Yizhuo; Liu, Tianhua; Xu, Ziqing; Dong, Ming (Frontiers in Oncology, 2023)
Objective Epstein-Barr virus (EBV) is a virus that is ubiquitous in humans. To investigate the association between EBV infection and lung cancer risk to reveal whether it is involved in the development and development of lung cancer. Although there has been discussion of EBV and lung cancer in the past. Through this study, we hope to deepen our understanding of the causes of lung cancer and provide new clues and targets for the prevention, early diagnosis and treatment of lung cancer. This study is also beneficial to the development of medical science and public health. First of all, the research results are expected to be incorporated into lung cancer prevention and treatment strategies and policies, so as to provide better treatment decisions for lung cancer patients and improve the survival rate and quality of life of patients. At the same time, communicating the research results to the public can help raise awareness of lung cancer risk factors. By encouraging healthy lifestyles and screening measures, the public can reduce their risk of lung cancer. In addition, this study also provides an important foundation for subsequent academic research and scientific exploration. It provides valuable information and inspiration for in-depth understanding of lung cancer and other related fields. Overall, this study makes an important contribution to both medical science and public health. Method By September 26, 2022, an online database was used to conduct a literature search in English. Random effects models were employed to estimate the prevalence of EBV with 95% confidence intervals (CIs). Additionally, the pooled odds ratio (OR) and 95%CI were calculated from case-control studies to determine the association between EBV and lung cancer. Results In this study of 886 patients with lung cancer, the overall prevalence of EBV infection was found to be 44.36% (95%CI: 4.08-16.9). Fourteen studies were included in the analysis, all of which used a case-control design and involved comparisons of tumors with adjacent or non-adjacent normal and non-cancerous controls. There was a significant difference in the prevalence of EBV infection in lung cancer tissues between China and other regions, with an odds ratio (OR) of 9.36 (95% confidence interval: 4.00-21.94, P<0.001, I²=73.5%). This suggests that the association between EBV infection and lung cancer cases is stronger in China than in other regions. Additionally, the prevalence of EBV infection varied across different pathological types of lung cancer, with rates of 81.08% for pulmonary lymphoepithelioma-like carcinoma (LELC),this a rare subtype of non-small cell lung cancer (NSCLC).34.78% for non-small cell lung cancer, and 21.17% for small cell lung cancer. The statistical analysis indicated that EBV infection was most significantly associated with cancer risk in LELC, while non-small cell lung cancer was more strongly associated with EBV than small cell lung cancer. Conclusion The study found that EBV infection increases the risk of lung cancer by more than four times, and this risk is associated with the pathological type, lymphatic infiltration, and degree of differentiation of the lung cancer, particularly in the rare subtype of pulmonary lymphoepithelioma in non-small cell lung cancer(NSCLC). Additionally, there are racial and regional differences in the correlation between EBV-infected lung cancer, with the Asian population showing greater susceptibility. The study used normal or abnormal tissue adjacent to the tumor as a control, which is considered a more accurate method for determining the relationship between EBV infection and lung cancer.